Feldspar's Influence on Clay Properties in Chan Neua Village, Chomphet District, Luang Prabang Province - PHAKVISETH, Pem; PHIMMAVONG, Kongsy; KEOBUAPHA, Laimaion; CHITDAVONG, Daolith; SENGPASEUTH, Bouthamaly; SACKDAVONG, Sinxay; Yang, Jongneng; KENENAVONG, Southida; VILAYSEANG, Soulina (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to study the effects of feldspar on clays used to forming ceramic products by studying, analyzing the physical and mechanical properties of the clay in Ban Chan Nuea, Chomphet District, Luan Prabang, Laos. Data and clay were collected from the village and washing, drying and grinding them finely. we were mixed with feldspar ore obtained from Hiem District, Huaphan Province in the ratio specified in the 6mixtures LF1 100%, LF2 90%, LF3 80%, LF4 70%, LF5 50%, LF6 30% clay, and feldspar ore is mixed to 100% in each mixture formula. Then put in an oven until dried. Then create a block sample and burn it at 5 temperatures 800 - 1250°C at 1 hour. Then test the density, strength, shrinkage, and water absorption. The results of this experiment found that feldspar is added in an amount of 50% or more, the surface of the clay will be white with a thin glassy coating. The physical properties test for water absorption is the highest percentage of water absorption was LF6 with 30% clay burned at 900°C with a water absorption rate of 20.33% and the sample with the lowest water absorption rate was LF6 with 30% clay at 1250°C with a water absorption rate of 0.20%. Shrinkage physical property testing at 1250°C, LF1 had the highest shrinkage 8.68% and LF4 had the lowest shrinkage 2.06%. The density at 1250°C LF5 has a minimum 1.71 g/cm3 and LF1 has a maximum 2.22 g/cm3, and the physical properties test in terms of hardness found that at 1250°C, LF6 has a minimum hardness 15.42 MPa and LF1 has a maximum hardness 91.21 MPa. According to the test results of all 6 mixture formulas and 5 temperatures, feldspar is used as an additive for the formation of ceramic clay.